Late drug‐resistance in mild MTLE: Can it be influenced by preexisting white matter alterations?. (20th April 2020) - Labate, Angelo; Caligiuri, Maria Eugenia; Fortunato, Francesco; Ferlazzo, Edoardo; Aguglia, Umberto; Gambardella, Antonio
Abstract: Objective: To identify early structural alterations preceding the development of drug‐resistance in mild mesial temporal lobe epilepsy (mMTLE), a drug‐responsive syndrome ideal for investigating epilepsy pathophysiology and potential prognostic markers of long‐term clinical outcome, using magnetic resonance imaging (MRI) at baseline and after 12‐year follow‐up. Methods: Since 2002, a total of 55 participants with a baseline diagnosis of mMTLE underwent three‐dimensional (3D) T1 1.5T MRI. Based on long‐term outcome (follow‐up 12 ± 3 years), we identified 39 patients with stable mMTLE (smMTLE) and 16 patients who had developed drug‐resistance overtime (refractory MTLE [rMTLE]). At follow‐up, 21 smMTLE and 13 rMTLE patients underwent 3T‐MRI including diffusion‐weighted scans. Structural images were processed using longitudinal voxel‐based morphometry and standard Freesurfer analysis. Statistical analyses were carried out accounting for age, age at onset, gender, hippocampal volume, and hippocampal sclerosis (Hs). Results: Patients presented similar demographic, clinical, and Hs features. White matter volume of the arcuate fasciculi, corticospinal tracts, left retrosplenial cingulum, and left inferior longitudinal fasciculus was reduced only in rMTLE patients before the development of drug‐resistance. At follow‐up, rMTLE showed decreased fractional anisotropy in the corpus callosum, superior longitudinal fasciculi, and major bundles of the right hemisphere. Significance: White matter temporal and extratemporal abnormalities are preexisting in patients with mild MTLE who will develop drug‐resistance, independently from the presence of Hs . Thus, these changes might be due to an inherited genetic alteration rather than a subordinate worsening after repeated seizures, multiple antiepileptic drugs, or initial precipitating factors.